PENGARUH MANAJEMEN RANTAI PASOK BERBASIS SISTEM ERP DALAM MENINGKATKAN KINERJA PT WISMILAK INTI MAKMUR TBK. - Huang, Chyntia; Novia, Jessica; Willyanto, Lia; Sisca, Veni; Cuandra, Fendy; Lalita, Nasar Buntu (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Every business actor who runs a business will establish relationships with other business actors. These relationships are formed into a chain known as a supply chain. In order for the company's supply chain activities to run optimally, of course a strategy is needed. One strategy that can be utilized is Enterprise Resource Planning (ERP). This study aims to determine the effect of ERP system-based supply chain management in improving the performance of PT Wismilak Inti Makmur Tbk. Quantitative and qualitative data analysis techniques were used in this study to process data into information. Where the data used is sourced from the annual report and company sales. From this research it can be seen that the supply chain of PT Wismilak Inti Makmur Tbk. This is complex because it involves various parties from the beginning of the process to the end of the distribution process, it can run effectively and because it has implemented several strategies, namely mitigation strategies, performance strategies and also the development of EVO diplomat products. In addition, the influence of the ERP system applied to the supply chain of PT Wismilak Inti Makmur Tbk. quite significant to the company's financial performance, namely inventory turnover, GPM, OPM, NPM, ROA, and ROE. These results are obtained from the results of the analysis of the company's financial statement data analysis with financial ratios.